The Application of Patriarchal Culture in the Scenes of the Film Nanti Kita Cerita Tentang Hari Ini - Desti Rahmadhini; Rustim; Edy Suisno (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research reveals the practice of patriarchal culture through narrative and cinematic character scenes in the film Nanti Kita Cerita Tentang Hari Ini, namely the character Narendra as a father who dominates women in domestic life. The purpose of this research is to find scenes of Narendra's character in dominating domestic life which is a representation of patriarchal culture. This research method uses a qualitative method with an interpretation approach to the patriarchal culture depicted by the director through narrative and cinematic aspects. Data collection techniques were carried out by observation, interviews and documentation. The results of this study show that the scenes built by the director through narrative and cinematic aspects show the practice of patriarchal culture and domination of women in domestic life. This research can contribute to how the director's experience of reading patriarchal culture and applying it in filmmakers' work practices in film language. Keywords: Patriarchy, Domination, Narrative, Cinematic.